APLIKASI KOMPOS SEBAGAI PUPUK ORGANIK UNTUK MENINGKATKAN KANDUNGAN FENOL PADA TANAMAN JAHE MERAH - Setiyo, Yohanes; Tika, I Wayan; -, Sumiyati; Suhendra, Lutfi (Agrotekno; Vol. 15, No. 2 Agustus 2009, 2012)
This research was aimed to optimize the production ofvolatile oil and oleoresin of red ginger crops by optimizingthe usage of compost as fertilizer. Compost was applied as anorganic fertilizer to red ginger crops in poly-bag withfertilization doses 0, 0.2, 0.4, 0.6, 0.8, and 1 kg for one kgcrops planting and red ginger was harvested at 8 and 9months after planting.Red ginger contained volatile oil of 3.8-3.97% DM, totalphenol of 5.7 - 6.4% DM, and ability to catch free radical ofDPPH compound of phenol of 2.5 - 2.6% DM. The quality ofthe red ginger was measured at the age of between 8 and 9months. Depended upon its volatile oil content, ability tocatch free radical DPPH compound of phenol, and its contenton phenol, hence harvest time of ginger could be minimizedto 8 months.
Keywords: composting, red ginger, organic material